(untitled) (International journal of artificial intelligence, 2025)
this article scientifically covers the introduction of modern pedagogical technologies in the training of specialists in the field of highways, the influence of innovative teaching methods on the educational process, and the application of digital solutions in the field. Recommendations are given on the advantages of integrating modern technologies into the educational process, the effectiveness of using scientific laboratories and artificial intelligence, as well as improving education based on international practice. Also discussed are the competency-based approach to the training of road construction specialists, the STEAM model, and teaching methods based on an innovative approach.